Advances in Echocardiographic Imaging in Heart Failure With Reduced and Preserved Ejection Fraction. Issue 2 (8th July 2016) - Omar, Alaa Mabrouk Salem; Bansal, Manish; Sengupta, Partho P.
Abstract : Echocardiography, given its safety, easy availability, and the ability to permit a comprehensive assessment of cardiac structure and function, is an indispensable tool in the evaluation and management of patients with heart failure (HF). From initial phenotyping and risk stratification to providing vital data for guiding therapeutic decision-making and monitoring, echocardiography plays a pivotal role in the care of HF patients. The recent advent of multiparametric approaches for myocardial deformation imaging has provided valuable insights in the pathogenesis of HF, elucidating distinct patterns of myocardial dysfunction and events that are associated with progression from subclinical stage to overt HF. At the same time, miniaturization of echocardiography has further expanded clinical application of echocardiography, with the use of pocket cardiac ultrasound as an adjunct to physical examination demonstrated to improve diagnostic accuracy and risk stratification. Furthermore, ongoing advances in the field of big data analytics promise to create an exciting opportunity to operationalize precision medicine as the new approach to healthcare delivery that aims to individualize patient care by integrating data extracted from clinical, laboratory, echocardiographic, and genetic assessments. The present review summarizes the recent advances in the field of echocardiography, with emphasis on their role in HF phenotyping, risk stratification, and optimizing clinical outcomes. Abstract : Supplemental Digital Content is available in the text.